Porosity-controlled TiNb2O7 microspheres with partial nitridation as a practical negative electrode for high-power lithium-ion batteries - Park, Hyunjung (2015)
Titanium niobium oxide (TiNb2O7) has been recognized as a promising anode material for lithium-ion batteries (LIBs) in view of its potential to operate at high rates with improved safety and high theoretical capacity of 387 mAh g−1. However, it suffers from poor Li+ ion diffusivity and low electronic conductivity originated from its wide band gap energy (Eg > 2 eV). Here, porous TiNb2O7 microspheres (PTNO MSs) are prepared via a facile solvothermal reaction. PTNO MSs have a particle size of ≈1.2 μm and controllable pore sizes in the range of 5–35 nm. Ammonia gas nitridation treatment is conducted on PTNO MSs to introduce conducting Ti1−xNbxN layer on the surface and form nitridated PTNO (NPTNO) MSs. The porous structure and conducting Ti1−xNbxN layer enhance the transport kinetics associated with Li+ ions and electrons, which leads to significant improvement in electrochemical performance. As a result, the NPTNO electrode shows a high discharge capacity of ≈265 mAh g−1, remarkable rate capability (≈143 mAh g−1 at 100 C) and durable long-term cyclability (≈91% capacity retention over 1000 cycles at 5 C). These results demonstrate the great potential of TiNb2O7 as a practical high-rate anode material for LIBs.